University Students and Balance : Investigating Social Support, Self-Efficacy, and Family Communication Patterns - Anthony, Kelly; Trusty, Shelby; Wiswell, Ashley; Knutson, Kristine (My University, 2019)
Current studies indicate that university students in the United States are experiencing mental health concerns, including stress, at rising rates. Students are expected to succeed in every area of their lives, whether it be attending class 12-18 hours a week, completing homework 24-36 hours per week, working a job, worrying about finances, enjoying college life by attending social events, making time to eat healthy and exercise, or getting the recommended 7-9 hours of sleep per night. The multiple demands placed on students are experienced as stress and can lead to feelings of imbalance. While the associations between stress and social support, self-efficacy, and family communication have been researched in the workplace, college-level student stress, and the factors that may mitigate it, have largely been ignored. This study surveys university students to look for possible relationships between these variables. Results can be used to help future university students alleviate stress and achieve balance.
Color poster with text, charts, and graphs.
Keywords: Mental health; Social support; College students; Posters; Department of Communication and Journalism